Assessing the naturalization degree of water in the Doce River through Grade of Membership (GoM) (Revista Espinhaço, 2015)
Water quality is an extremely important topic to many scientific fields and also to the environmental management. Therefore, working with new paths to address the water quality is as challenging as relevant. The regular approach to the theme is the WQI, a worldwide-recognized model that integrates nine parameters. Although, the hardness of the WQI lead to gaps of interpretation. Assuming that the fuzzy logic can be an in-depth tool to reach the complexity of water quality, this work brings a methodological proposal to use the Grade of Membership method to measure the naturalization of water. This algorithm can indicate how closer any water sample is to a given pristine pattern. It was used 16 years of physical, chemical and biological parameters of water, sampled by trimester in 99 stations along the Doce River watershed. The results show that all samples are far from their pristine condition. Besides, almost all cases have some grade of membership to the three classes (good, medium and bad). The model was successfully applied, promoting a classification of the degree of naturalization of water. Furthermore, the fuzzy logic allows discussing the data beyond the classes, pointing the farther parameters to its pristine condition and guiding to a more efficient water and environmental management.
Keywords: water quality; naturalization; GoM; classification